2022
DOI: 10.1177/0032258x221142525
|View full text |Cite
|
Sign up to set email alerts
|

Improving child sexual exploitation material investigations: Recommendations based on a review of recent research findings

Abstract: Child sexual exploitation material (CSEM) investigations have emerged as an area of specialization that combines multiple skillsets. Recent research has reshaped how we view CSEM offenders – they have different offense-supportive cognitions from contact sex offenders, their use of technology is no longer based on anecdotal evidence, and approaches to investigative planning, interviewing and forensics have evolved. This paper summarizes select, relevant areas of recent research related to CSEM investigations, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
6
0
2
Order By: Relevance
“…The qualitative data reinforce the severity of content and volume of data, with the severity of CSEM discussed in a more emotional and victim-focused manner (e.g., I can hear the children screaming in my head after work), and the volume was discussed in a more cognitive and system-focused manner (e.g., having high workload and limited resources). As disengaging from the emotional aspects and the victim is associated with better wellbeing among law enforcement personnel, agencies should presumably evaluate if some specific parts of the job that increase the emotional involvement (e.g., sounds) are necessary or can be removed from the investigation process (Steel et al, 2022). At the same time, agencies should make sure they have the resources to support law enforcement personnel that are emotionally overwhelmed and provide resilience training (Steel et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative data reinforce the severity of content and volume of data, with the severity of CSEM discussed in a more emotional and victim-focused manner (e.g., I can hear the children screaming in my head after work), and the volume was discussed in a more cognitive and system-focused manner (e.g., having high workload and limited resources). As disengaging from the emotional aspects and the victim is associated with better wellbeing among law enforcement personnel, agencies should presumably evaluate if some specific parts of the job that increase the emotional involvement (e.g., sounds) are necessary or can be removed from the investigation process (Steel et al, 2022). At the same time, agencies should make sure they have the resources to support law enforcement personnel that are emotionally overwhelmed and provide resilience training (Steel et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…As disengaging from the emotional aspects and the victim is associated with better wellbeing among law enforcement personnel, agencies should presumably evaluate if some specific parts of the job that increase the emotional involvement (e.g., sounds) are necessary or can be removed from the investigation process (Steel et al, 2022). At the same time, agencies should make sure they have the resources to support law enforcement personnel that are emotionally overwhelmed and provide resilience training (Steel et al, 2022). For those that may not naturally disengage from emotional reactions related to CSEM content, the strategy of emotional distancing may be particularly difficult to both learn and enact.…”
Section: Discussionmentioning
confidence: 99%
“…(p. 36)Studies of this sort are few and far between. A recent study by Steel et al (2022), however, does note that:Current CSEM offenders are also significantly more mobile in their viewing habits than they were a decade ago. In a recent study, 22% of offenders reported viewing CSEM at a hotel/motel, 9% from a vehicle, 9% at work and 99% at home.…”
Section: Risk Assessmentmentioning
confidence: 92%
“…(p. 36) Studies of this sort are few and far between. A recent study by Steel et al (2022), however, does note that:…”
Section: Potentially Outdated Samplesmentioning
confidence: 95%
See 1 more Smart Citation